إشكالية السلوك الاتصالي داخل المؤسسة والتنشئة الاجتماعية للأفراد - فرحاتى، فاطيمة Ferhati, Fatimah (جامعة باتنه 1 - كلية العلوم الإسلامية, 2020)
يعتبر الاتصال أحد أهم الركائز التي تقوم عليها المؤسسات باعتباره شريان الحياة فيها وارتباط ارتفاع مستوى كفاءتها بنجاح هذا الاتصال وفاعليته، لكن نجد داخل المؤسسات الجزائرية عدة عوامل تعرقل العملية الاتصالية وتشوبها الكثير من المشاكل التي تحول دون نجاعته لعدة أسباب مختلفة منها ما له علاقة بمسائل تنظيمية وأخرى بخلفيات ثقافية ذات علاقة بالتنشئة الاجتماعية للإفراد في المؤسسة باعتبارها تنظيم اجتماعي، وباعتبار الاتصال سلوك إنساني بالدرجة الأولى، عملت هذه الدراسة على البحث فيما مدى علاقة السلوك الاتصالي داخل المؤسسة بأساليب التنشئة الاجتماعية، وتنبع أهمية الدراسة من أهمية الموضوع في حد ذاته لأن موضوع الاتصال يعد من أهم المواضيع التي اهتم بها المختصون، فالاتصال سواء كان في مؤسسة ذات طابع صناعي أو خدماتي يعتبر أحد أهم العناصر التي يرتكز عليها عملها على كل المستويات، حيث يعمل على إحداث التنسيق بين مختلف الأطراف والمستويات داخل المؤسسات في نقل المعلومات والأوامر وهو ينمي العلاقات الاجتماعية والإنسانية ويستطيع أن يصل بالعمال لإدراك دورهم وأهميتهم في تحقيق أهداف مؤسستهم وبالتالي تحفيزهم أكثر للاجتهاد والمزيد من العطاء، كما يعتبر من أبرز دعائم المؤسسة في اتخاذ القرارات.
Communication is one of the most important pillars of the foundations of institutions being a vital aspect, its correlation with its high level of efficiency is related to the success and effectiveness of this connection. But we find within the Algerian institutions several factors that hamper the communication process and a lot of problems that prevent its effectiveness. Several reasons, including those related to organizational issues and others related to cultural backgrounds affilliated to the socialization of individuals in the institution as a social organization. Moreover, considering the communication as a human behavior in the first place, this study investigates the relationship of communication behavior within the institution with the methods of socialization. The importance of the study stems from the importance of the topic of communication that concerned specialists, communication, whether in an industrial or service-oriented institution is one of the most important elements on which the institutions base their works on at all levels. Considering it as a social system the communication works to develop coordination between different parties and levels within the institutions in the transfer of information and orders, it develops social and human relations and can help the workers to realize their role and importance in achieving the objectives of their institution and thus motivate them for more diligence and tender, it is viewed as one of the main pillars of the institution in making decisions.
Keywords: التنشئة الاجتماعية -- العمليات الإدارية -- إدارة الأفراد -- الاتصال التنظيمي